If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3u-1)+8u+5=6(u-5)-3u
We move all terms to the left:
2(3u-1)+8u+5-(6(u-5)-3u)=0
We add all the numbers together, and all the variables
8u+2(3u-1)-(6(u-5)-3u)+5=0
We multiply parentheses
8u+6u-(6(u-5)-3u)-2+5=0
We calculate terms in parentheses: -(6(u-5)-3u), so:We add all the numbers together, and all the variables
6(u-5)-3u
We add all the numbers together, and all the variables
-3u+6(u-5)
We multiply parentheses
-3u+6u-30
We add all the numbers together, and all the variables
3u-30
Back to the equation:
-(3u-30)
14u-(3u-30)+3=0
We get rid of parentheses
14u-3u+30+3=0
We add all the numbers together, and all the variables
11u+33=0
We move all terms containing u to the left, all other terms to the right
11u=-33
u=-33/11
u=-3
| 3n+3=162 | | .5x+8=2x | | 3x-3+12=7x+8x+10 | | x/5=x/7-12 | | 10y-2y=40 | | -18j+15=-14-18j | | 4y-9+y+35=8y+30-5y | | -2/3=-2/5+s | | 25=x/3+2 | | -18j+15= | | 4x(50+20)+110=200 | | (x2-3x)-(10x-x2=) | | y+10y=0 | | -4x-6=-4x-6 | | x^2-12x+111=0 | | 3(5r-5)=6(-3+3r) | | -4+10l=-6 | | 7x+3=-158 | | 5x-(3x+8)=4x-38 | | 3x(x-1)+8(x-3)=6x+7-5x | | 3(5r-5)=6(-3{3r) | | ((2z-3)/5)-((z-6)/4)=3 | | x+3/2=5/2 | | m+-6+-2m=78 | | -6n+6(-7-8n)=2+5(-4n-2) | | 25(1-x)=-8-9 | | -p+13=-p+2 | | 66=1/3×3.14×25×h | | -x^2-11x=10 | | -2x(x+1)=30 | | 76=-4+4x | | -5+10e=5 |